Assessing impacts of agricultural research for development: A systemic model focusing on outcomes. Issue 2 (2nd March 2018) - Temple, Ludovic; Barret, Danielle; Blundo Canto, Genowefa; Dabat, Marie-Hélène; Devaux-Spatarakis, Agathe; Faure, Guy; Hainzelin, Etienne; Mathé, Syndhia; Toillier, Aurelie; Triomphe, Bernard
Abstract: Over the past decade, renewed societal demands on public research have been structured by various generic issues, while others are specific to the context of developing countries. In the first part of this article, after reviewing those issues, we examine how they reshape the analytical frameworks that structure the understanding of causal relationships between research activities, innovation processes, and the consequences of both for development. We used an impact pathway framework to assess innovation processes by looking at 13 case studies on research in agricultural and food sectors of developing countries. The results show the diversity of outcomes related to human capital, social capital, and knowledge infrastructure. Moreover, they show the systemic interaction between outputs, outcomes, and impacts. Based on this assessment, we demonstrate that the way impact pathways are framed and analysed needs to be improved to better consider the complex interactions between the diverse actors involved in innovation processes. Through a discussion of our results, we propose an analytical framework to help improve impact assessment methods for research activities.